An Extensive Stanford Type A Aortic Dissection Involving Bilateral Carotid and Iliac Arteries - E. W. Lee; N. Jourabchi; S. C. Sauk; D. Lanum (Case Reports in Radiology)
We present a rare case of continuous, extensive aortic dissection (AD) involving the bilateral common carotid arteries, the ascending, thoracic, and abdominal aorta, and bifurcation of the right common iliac artery. A 61-year-old man with history of chronic hypertension presented with a one-day history of chest pain, vertigo, left facial drooping, and left hemiparesis. Despite the presence of bilateral carotid bruits, doppler ultrasound of the neck was postponed, and the patient was treated with thrombolytic therapy for a presumed ischemic stroke. The patient's symptoms began to resolve within an hour of treatment, at which time treatment was withheld. Ultrasound performed the following day showed dissection of bilateral common carotid arteries, and CT angiography demonstrated extensive AD as described earlier. The patient subsequently underwent cardiovascular surgery and has been doing clinically well since then. AD has a myriad of manifestations depending on the involvement of aortic branches. Our paper illustrates the importance of having a high index of suspicion for AD when a patient presents with a picture of ischemic stroke, since overlapping signs and symptoms exist between AD and stroke. Differentiating between the two conditions is central to patient care as thrombolytic therapy can be helpful in stroke, but detrimental in AD.